We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
126
1
avatar+895 

Prove these identities.

 May 11, 2019
 #1
avatar+103789 
+1

Here's my best effort :

 

74.   cos ( θ + k π)  =

 

cosθ   cos kπ   -  sin θ  sin π  =

 

cos θ cos kπ

 

If  k is even  then     cos kπ  =  1 ...... so cos θ * (1)  =   (-1)kcosθ   

If k is odd   then    cos kπ  =  -1 ...... so cos θ * (-1)  =   (-1)kcosθ

 

 

cool cool cool

 May 11, 2019

31 Online Users

avatar
avatar
avatar